The Identification of a Novel Nucleomodulin MbovP467 of Mycoplasmopsis bovis and Its Potential Contribution in Pathogenesis - Abdul Raheem; Doukun Lu; Abdul Karim Khalid; Gang Zhao; Yingjie Fu; Yingyu Chen; Xi Chen; Changmin Hu; Jianguo Chen; Huanchun Chen; Aizhen Guo (Cells, 2024)
Mycoplasmopsis bovis is a causative agent of crucial diseases in both dairy and beef cattle leading to substantial economic losses. However, limited control measures for M. bovis-related diseases exist due to a lack of understanding about the virulence factors of this pathogen, a common challenge in mycoplasma research. Consequently, this study aimed to characterize a novel nucleomodulin as a virulence-related factor of M. bovis. Employing bioinformatic tools, we initially predicted MbovP467 to be a secreted protein with a nuclear localization signal based on SignalP scores and the cNLS (Nuclear Localization Signal) Mapper, respectively. Subsequently, the MbovP467 gene was synthesized and cloned into a pEGFP plasmid with EGFP labeling to obtain a recombinant plasmid (rpEGFP-MbovP467) and then was also cloned in pET-30a with a consideration for an Escherichia coli codon bias and expressed and purified for the production of polyclonal antibodies against the recombinant MbovP467 protein. Confocal microscopy and a Western blotting assay confirmed the nuclear location of MbovP467 in bovine macrophages (BoMacs). RNA-seq data revealed 220 up-regulated and 20 down-regulated genes in the rpEGFP-MbovP467-treated BoMac group compared to the control group (pEGFP). A GO- and KEGG-enrichment analysis identified associations with inflammatory responses, G protein-coupled receptor signaling pathways, nuclear receptor activity, sequence-specific DNA binding, the regulation of cell proliferation, IL-8, apoptotic processes, cell growth and death, the TNF signaling pathway, the NF-κB signaling pathway, pathways in cancer, and protein families of signaling and cellular processes among the differentially expressed up-regulated mRNAs. Further experiments, investigating cell viability and the inflammatory response, demonstrated that MbovP467 reduces BoMac cell viability and induces the mRNA expression of IL-1β, IL-6, IL-8, TNF-α, and apoptosis in BoMac cells. Further, MbovP467 increased the promoter activity of TNF-α. In conclusion, this study identified a new nucleomodulin, MbovP467, for M. bovis, which might have an important role in M. bovis pathogenesis.